1996
DOI: 10.1074/jbc.271.52.33433
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel β-N-Acetyl-D-glucosaminidase from Vibrio furnissii

Abstract: ) describe two unique ␤-N-acetylglucosaminidases from Vibrio furnissii. A third, ExoII, is reported here. The gene, exoII, was cloned into Escherichia coli, sequenced, and ExoII purified to apparent homogeneity (36 kDa). The molecular weight and N-terminal 16 amino acids of the protein conform to the predicted sequence. ExoII exhibited unique substrate specificity. It rapidly cleaved p-nitrophenyl and 4-methylumbelliferyl ␤-GlcNAc, was slightly active with p-nitrophenyl-␤-GalNAc, and was inactive with all othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
2
54
1
Order By: Relevance
“…On the other hand, Chitlaru and Roseman also reported that -N-acetylglucosaminidase (ExoII) from V. furnissii is a cytoplasmic enzyme which has no activity towards any of the chitin oligosaccharides. 33) They speculated that ExoII might produce phenol derivatives that induce V. furnissii to invade invertebrate cuticles. Therefore, NagC is the first reported example of a cytoplasmic -N-acetylglucosaminidase involved in the chitin degradation system.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chitlaru and Roseman also reported that -N-acetylglucosaminidase (ExoII) from V. furnissii is a cytoplasmic enzyme which has no activity towards any of the chitin oligosaccharides. 33) They speculated that ExoII might produce phenol derivatives that induce V. furnissii to invade invertebrate cuticles. Therefore, NagC is the first reported example of a cytoplasmic -N-acetylglucosaminidase involved in the chitin degradation system.…”
Section: Discussionmentioning
confidence: 99%
“…In this enzyme, Asp285 in the N-terminal domain and Glu491 in the C-terminal domain are considered to be involved in catalysis as nucleophile and proton donor, respectively. [12][13][14] Based on this finding, a putative active site of Nags in this family was also deduced to be Asp242 of Vibrio furnissii ExoII 10) and Asp303 of C. paraputrificum Nag3A, 6) corresponding to Asp285 of ExoI. 12) However, another active site, a putative proton donor, was not expected in single-domain enzymes, including C. paraputrificum Nag3A, from the information about barley ExoI, since Nag3A and other single-domain enzymes of family 3 did not contain a second domain.…”
Section: Circular Dichroism Of Wild-type and Mutant Nagsmentioning
confidence: 99%
“…6,[9][10][11] From the alignment of the catalytic domains of the 12 Nags (Fig. 1), it can be seen that two Glu residues and six Asp residues are highly conserved among them and are candidates for catalytic amino acid residues.…”
mentioning
confidence: 99%
“…The enzymatic breakdown of chitin by chitinases has been reported from our laboratory [9,10] as well as from others [11][12][13][14][15]. The chitinase gene (chi) of Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%